(untitled) (Revista de Educação Continuada em Medicina Veterinária e Zootecnia do CRMV-SP, 2013)
A number of reports describe limited numbers of animals inoculated intentionally with rabies virus that do not become ill and may have little to no detectable antibody while other conspecific individuals succumb to the same inoculum. This review will detail methods used in measuring immunity and optimal method validation, in relation to potential identification of baseline susceptibility, enhanced disease diagnosis, and optimal prevention practices for humans and animals. Potential factors for successful rabies virus infection include: 1) protection of infected neurons from host immunemediated destruction by the inhibition of virus-mediated apoptosis and overexpression of immune-subversive molecules resulting in killing or inactivation of ‘protective’ T cells migrating into the infected nervous system; 2) an hypothesis that lethality results from neuronal dysfunction inhibiting proteins required for neuronal maintenance; 3) a posit that virus phosphoprotein and host cell dynein light chain 8 interaction may regulate viral ribonucleoprotein linking to cell transport; 4) a thesis that innate immunity, paradoxically, favors rabies virus neuro-invasiveness through enhanced infiltration and promotion of CD8(+) T cell elimination; and then alternatively that ; 5) type I IFN produced in the rabies virus-infected nervous system reduces neuroinvasiveness and partially protects from fatal infection. It is clear that innate immune cells detect pathogens, most likely including rabies virus, via pattern recognition receptions, such as Toll-like receptors and others. Pathogen-associated molecular patterns activate receptors which induce production of pro-inflammatory cytokines and signals to activate inflammation. In addition, these receptors are required for an adaptive immune response. Innate and adaptive immune responses act as two interlocking defense lines. Following a rabies exposure, virus may be initially suppressed by innate immunity accompanied by effector T cell recruitment for activation of adaptive immunity. Alternatively, the uniquely high mortality rate of successful rabies virus infection may be due to virus-host interactions that remain largely a mystery. The accurate and precise measurement of an adaptive immune response may be defined by experimental methods or well-described methods, such as the rapid fluorescent focus antibody test, as performed and fully validated in some laboratories. The interpretation of findings based on these various methods should be in relation to clinical observations and collaborative investigation of unique, isolated, novel findings. The fine-tuning, interaction, and timing of innate and adaptive host responses and the methods used for detection and measurement, will require dedicated investigation towards optimal disease prevention.